WIĘZI RODZINNE W PROCESIE POZYTYWNEGO I AKTYWNEGO STARZENIA SIĘ - Adamczyk, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Family is the basic environment for emotional and life activity of the elderly. In Poland, the family is still the main source of assistance to the older people both in terms of their emotional activity and satisfying their basic necessities. Despite the changes, which modern family undergoes, it is still the most suitable place for positive ageing, as it continues to offer to the older people the support in four major areas, that is, in economic, socialisation, educational/cultural and emotional/expressive aspects of their lives. The aim of this article is to bring the issue of the impact of the ageing process on changes in roles played by old people as well as to show progressive changes in family relationships due to the ageing of individual family members. The article attempts to create different family models, discussing directions of assistance and quality of support provided by the family.